Exploring pre-service special needs teachers’ assessment conceptions and assessment self-efficacy - Kyttälä Minna; Björn Piia Maria; Rantamäki Milla; Närhi Vesa; Aro Mikko (Routledge, Taylor & Francis Group, 2022)
This survey study (N = 148) investigates the interrelationships between assessment conceptions, assessment self-efficacy, prior education, and teaching experience amongst Finnish pre-service special educational needs teachers (pre-service SENs). The results showed that assessment conceptions and assessment self-efficacy are intertwined. Assessment conceptions, prior studies, and teaching experience were clustered into three different pre-service SEN types: Assessment Positives, Assessment Cautious, and Assessment Criticals. Pre-service SENs with assessment-positive or assessment-cautious conceptions reported higher assessment self-efficacy than students with assessment-critical conceptions. Practical implications are discussed.